2012
DOI: 10.1523/jneurosci.5604-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced NMDA Receptor-Dependent Thalamic Excitation and Network Oscillations in Stargazer Mice

Abstract: Disturbances in corticothalamic circuitry can lead to absence epilepsy. The reticular thalamic nucleus (RTN) plays a pivotal role in that it receives excitation from cortex and thalamus, and when strongly activated can generate excessive inhibitory output and epileptic thalamocortical oscillations that depend on post-inhibitory rebound. Stargazer mice (stg) have prominent absence seizures resulting from a mutant form of the AMPAR auxiliary protein stargazin. Reduced AMPAR excitation in RTN has previously been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 93 publications
(156 reference statements)
3
55
1
Order By: Relevance
“…Consistent with our current observations, it has been reported that TRN neurons in epileptic genetic absence epileptic rats from Strasbourg (GAERS) rats displayed higher excitability, higher firing frequency, and regularity (34). In parallel with these results from GAERS rat, stargazer mice (another genetic model for absence seizures) showed hyperexcitable TRN neurons due to an enhanced NMDA receptor (35). Thus, several gene mutation models of absence seizures show altered TRN excitability.…”
Section: Methodssupporting
confidence: 92%
“…Consistent with our current observations, it has been reported that TRN neurons in epileptic genetic absence epileptic rats from Strasbourg (GAERS) rats displayed higher excitability, higher firing frequency, and regularity (34). In parallel with these results from GAERS rat, stargazer mice (another genetic model for absence seizures) showed hyperexcitable TRN neurons due to an enhanced NMDA receptor (35). Thus, several gene mutation models of absence seizures show altered TRN excitability.…”
Section: Methodssupporting
confidence: 92%
“…Similar to the GRIA4 knockout model, this synapse-specific mistrafficking of AMPA receptors in stargazer mice could lead to a loss of fast corticothalamic feedforward inhibition. However, while the faster AMPA receptor-mediated activation of the RTN is reduced (Menuz and Nicoll, 2008), the slower, NMDA receptor-mediated activation of the RTN is enhanced, providing a potential mechanism for recruitment of tonic inhibition in the thalamus (Lacey et al, 2012). Isolated stargazer cortical slices are also hyperexcitable (Di Pasquale et al, 1997), but whether there is also impaired feedforward inhibition or enhanced tonic inhibition in the cortex has not yet been determined.…”
Section: Ampa Receptor-related Mutations: Silencing Fast Feedforward mentioning
confidence: 99%
“…Experiments in commonly used spontaneous inbred genetic mouse models of absence seizures (tottering, lethargic, stargazer) were performed in both males and females without any reported sex-dependent differences in the frequency of absence seizures (Aizawa et al, 1997; Noebels and Sidman, 1979; Lacey et al, 2012). Moreover, studies of atypical absence epilepsy phenotypes generated in mice transgenically overexpressing GABA B receptor R1a or Ra1b subunits did not report sex-dependent effects (Aizawa et al, 1997; Lacey et al, 2012; Noebels and Sidman, 1979; Stewart et al, 2009; Wu et al, 2007). Pharmacologically-evoked absence seizures in mice have been produced through the systemic administration of GABA A R antagonists and GABA B R agonists.…”
Section: Sex Differences In Mouse Models Of Typical and Atypical Absementioning
confidence: 99%